Local knowledge of medicinal plants in sub-ethnic Batak Simalungun of North Sumatra, Indonesia - MARINA SILALAHI; JATNA SUPRIATNA; EKO BAROTO WALUJO; NISYAWATI NISYAWATI (Biodiversitas Journal of Biological Diversity, 2015)
Silalahi M, Supriatna J, Walujo EB, Nisyawati. 2015. Local knowledge of medicinal plants in sub-ethnic Batak Simalungun of North Sumatra, Indonesia. Biodiversitas 16: 44-54. Research on the local knowledge of medicinal plants by sub-ethnic BatakSimalungun of North Sumatra was conducted, using an ethnobotanical approach. The sample consisted of 8 key informants and 32general respondents, who were grouped into two, namely those who were 30-50 years old and >50 years old. Data were analyzed bothqualitatively by descriptive statistics and quantitatively by calculating the index of cultural significance (ICS) and the use value (UVs).It was found that 239 species (170 genera, 70 families) of medicinal plants were used to cure 18 kinds of natural diseases and 2 kinds ofsupra natural diseases. Almost half of those plants (119 species) had leaves used as medicines. Among the diseases, gastrointestinaldisorders had the highest number of medicinal plants used (72 species), followed by fever (64 species), and fractures (41 species). Itseemed that younger generation had lost their knowledge in the medicinal plants because their knowledge of medicinal plants (48.19 ±8.35 species) was lower than the that of older generation (170.19 ± 18.38 species), while our key informants had the highest knowledgeof medicinal plants among respondents (202.00 ± 12.32 species).